Continuous coordination within the context of cooperative and human aspects of software engineering - Al-Ani, Ban; Trainer, Erik; Ripley, Roger; Sarma, Anita; van der Hoek, Andre; Redmiles, David (International Conference on Software Engineering 2008, 2008)
We have developed software tools that aim to support the cooperative software engineering tasks and promote an awareness of social dependencies that is essential to successful coordination. The tools share common characteristics that can be traced back to the principles of the Continuous Coordination (CC) paradigm. However, the development of each sprung from carrying out a different set of activities during its development process. In this paper, we outline the principles of the CC paradigm, the tools that implement these principles and focus on the social aspects of software engineering. Finally, we discuss the socio-technical and human-centered processes we adopted to develop these tools. Our conclusion is that the cooperative dimension of our tools represents the cooperation between researchers, subjects, and field sites. Our conclusion suggests that the development processes adopted to develop like-tools need to reflect this cooperative dimension.